Influence of electronic word-of-mouth on repurchase intention among ShopeeFood users in Padang City: The mediating role of brand Image - Yuli Sandra, Reza; Evanita, Susi (Universitas Negeri Padang, 2025)
This research purposes to analyze the effect of Electronic Word of Mouth on Repurchase Intention with Brand Image as a mediating variable for ShopeeFood users in Padang City. The population in this research were citizens of Padang City who knew and had made purchases through the ShopeeFood online food delivery service at least twice. The sample in this study were 153 respondents. Data collection was carried out by distributing questionnaires online via Google Form and data processing using SmartPLS software. Based on the research results, it is concluded that (1) Electronic Word of Mouth has a positive and significant effect on Repurchase Intention (2) Electronic Word of Mouth has a positive and significant effect on Brand Image (3) Brand Image has a positive and significant effect on Repurchase Intention (4) Electronic Word of Mouth has a positive and significant effect on Repurchase Intention mediated by Brand Image.